Die geskiedenis, ontwikkeling en toepassing van gesondheidsvoorligting in die daghospitale-organisasie - Virginia J. Meyer (AOSIS, 1980)
The development and implementation of health education began on a small scale in 1975 by involving children in certain educational games. The zeal and active participation of the children stimulated the interest of the parents and it became obvious that the health education programme would have to be extended to involve all patients of all age groups. Simple methods were devised to educate patients on various health aspects and their positive reaction to these programmes resulted in the expansion of the health education services to the community and which is still expanding according to needs.